Pengaruh Audit Tenure, Ukuran Perusahaan dan Komite Audit Terhadap Audit Report Lag: (Studi Pada Perusahaan Property & Real Estate yang Terdaftar di Bursa Efek Indonesia Tahun 2019-2022) - Faradilla Kurnia, Rani; Harry Mukti, Aloysius; Hasioan Sianipar, Panata Bangar (Baashima : Jurnal Bisnis Digital, Akuntansi, Kewirausahaan, dan Manajemen, 2024)
This study aims to examine The Effect of Audit Tenure, Company size and Audit Committee on Audit Report Lag. The population in this study is all Property and Real Estate Companies listed on the Indonesia Stock Exchange in 2019-2022. The variables used in this study are Audit Report Lag as the dependent variable; Audit Tenure, Company Size, and Audit Committee as an independent variable. The sampling technique used is the purposive sampling method and obtained as many as 89 companies and 225 samples. The analysis methods used are Descriptive Statistical Analysis, Classical Assumption Test, Correlation Test, Multiple Linear Regression Test, and Hypothesis Test. The results showed that the Audit Tenure and Audit Committee did not affect Audit Report Lag. And Company Size harm Audit Report Lag.